Pengaruh Minat Baca dan Sumber Belajar terhadap Hasil Belajar IPS Siswa Kelas VIII SMP Negeri 5 Kota Solok - Anjany, Noviya; Basyirun, Fajri (Jurusan PIPS FKIP UMMY Solok, 2023)
This research was motivated by the low learning outcomes of students in social studies subjects at SMP Negeri 5 Solok City. This is thought to be due to low interest in reading and learning resources in the learning process. This research aims to examine, 1) the influence of interest in reading on the social studies learning outcomes of class VIII students at SMP Negeri 5 Solok City, 2) the influence of learning resources on the social studies learning outcomes of class VIII students at SMP Negeri 5 Solok City, 3) the influence of interest in reading and Learning Resources for Social Studies Learning Outcomes for Class VIII Students at SMP Negeri 5 Solok City. This research method is a quantitative method. The subjects in this research were class VIII students at SMP Negeri 5 Solok City. Data collection is carried out through questionnaires, observation and documentation. From the research results it was found that 1) there was no partial influence between interest in reading on the social studies learning outcomes of class VIII students of SMP N 5 Solok City, 2) there was no influence between learning resources on the social studies learning outcomes of class VIII students of SMP N 5 Solok City and, 3) there is no simultaneous influence between reading interest and learning resources on students' social studies learning outcomes class VIII SMP N 5 Solok City.